Supplementation with Tex261 provides a possible preventive treatment for hypoxic pulmonary artery hypertension - Chen, Shaokun; Wei, Xiaozhen; Zhang, Xu; Yao, Mengge; Qiu, Zhihuang; Chen, Liangwan; Zhang, Li (Frontiers in Pharmacology, 2022)
Objectives: Pulmonary artery hypertension (PAH) is a serious disease for which there is no effective treatment. Its pathogenesis is complex and has not yet been clarified. Tex261 is a protein-coding gene whose functional enrichment nodes include the transporter activity of COP II. However, the role of Tex261 in PAH remains unknown. Methods: Sugen5416/Hypoxic PAH models were established, and pulmonary arteries (PAs) were isolated for proteomic sequencing. The binding sites between Hif-1α and Tex261 were verified by dual-luciferase reporter gene assay. Cell proliferation was detected by MTS and EdU assays. For determination of the preventive and therapeutic effects of Tex261, intratracheal instillation of adeno-associated virus (AVV6) with Tex261 vectors was performed. Results: Tex261 was screened according to the proteomic sequencing data. Hif-1α inhibited Tex261 promoter activity under hypoxia. Decreased Tex261 expression promoted PASMC proliferation. Tex261 regulated Sec23 via the Ndrg1-mediated Akt pathway. Tex261 overexpression improved the pressure and vessel remodeling of PAs induced by Sugen5416/hypoxia. Conclusions: Hypoxia suppressed Tex261 expression through Hif-1α activation. The decreased Tex261 could promote Ndrg1 and depress Akt activity and then inhibit Sec23 activity, which leads to cell proliferation and vessel remodeling. Elevated Tex261 has some preventive and therapeutic effects on rats with PAH.